Deconstruction of archetypal structures in the images of antiheroes in fantasy works among sociology students - A. A. Tretiakova (Вестник университета)
The sociology of cinema is one of the most significant areas within the sociology of culture, since cinema and television (hereinafter referred to as TV) series are a mass and most accessible form of art. However, the degree of development of the problems of the sociology of cinema, especially in the theoretical context, remains insufficient given the social significance. One of the areas within which a successful study of cinema and TV series is possible is constructionism, which allows us to study narratives, images, and the transformation of public opinion under the influence of cinema, and vice versa. In this case, the study of film characters is one of the most important parts of the study of cinema from the point of view of sociological theory. Therefore, the study implements the task of studying the development of the topic of representation of film characters from the point of view of social constructionism, and describes the results of a sociological survey devoted to the study of the perception of the characteristics of characters in fantasy films and TV series. Analysing the level of recognition and the content of students’ ideas about the characteristics of the characters, the author classifies them based on the severity of qualities. Based on the classification of the most frequently identified characteristics of characters in various groups, the typical positive and negative characteristics of antiheroes in the fantasy genre are determined. As a result, the author has come to the conclusion that the uniqueness of fantasy characters in general and antiheroes in particular lies in the fact that their characteristics are constituted of moral, strong-willed, intellectual and other qualities, unlike characters in other genres, where factors related to the possibility of association with social groups and external attributes are also important.